2021
DOI: 10.1038/s41467-020-20687-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of COVID-19 intervention scenarios for São Paulo—Brazil

Abstract: With COVID-19 surging across the world, understanding the effectiveness of intervention strategies on transmission dynamics is of primary global health importance. Here, we develop and analyze an epidemiological compartmental model using multi-objective genetic algorithm design optimization to compare scenarios related to strategy type, the extent of social distancing, time window, and personal protection levels on the transmission dynamics of COVID-19 in São Paulo, Brazil. The results indicate that the optima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Compared to RL, evolutionary algorithms are easier to implement because the loss functions are easier to model and the algorithms are easy to train in parallel. Despite the fact that genetic algorithms (GA) are the most common evolutionary method (Pinto Neto et al, 2021; Miralles-Pechuán et al, 2020; Zhang G, 2021), we observed that they had high divergence caused by local optimums. Therefore, to obtain more reliable solutions, we decided to change our optimizer to Evolutionary Strategies (ES).…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Compared to RL, evolutionary algorithms are easier to implement because the loss functions are easier to model and the algorithms are easy to train in parallel. Despite the fact that genetic algorithms (GA) are the most common evolutionary method (Pinto Neto et al, 2021; Miralles-Pechuán et al, 2020; Zhang G, 2021), we observed that they had high divergence caused by local optimums. Therefore, to obtain more reliable solutions, we decided to change our optimizer to Evolutionary Strategies (ES).…”
Section: Methodsmentioning
confidence: 74%
“…Pinto Neto et al (2021) used a multi-objective GA design optimization on a epidemiological compartmental model, named SUEIHCDR, to compare scenarios related to strategy type, the extent of social distancing, time window, and personal protection levels on the transmission dynamics of COVID-19 in São Paulo, Brazil. Their results indicated that the ability to reduce social distancing depends on a 5–10% increase in the current percentage of people strictly following protective guidelines, highlighting the importance of protective behavior in controlling the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Metaheuristic optimization approaches have also been applied to solve the optimal control strategies of the pandemic. These strategies range from the implementation of social distancing to reach herd immunity [163,164], to increasing testing and quarantine requirements [165], and to developing traditional Chinese medicine (TCM) prevention programs [166]. In [165], the authors developed a nature-inspired model to simulate the distribution process of COVID-19 in different countries and strive to maximize the number of "safe" countries (those that are immune to COVID-19).…”
Section: Prevention and Control: Curbing The Spread And Mitigating The Effectsmentioning
confidence: 99%
“…Mathematical models have been previously used with greater success in understanding the transmission dynamics and control mechanisms of infectious diseases [ 11 ]. To understand the early transmission dynamics of COVID-19 under different scenarios, a number of mathematical models have been previously proposed [ 12 21 ]. These established epidemiological and mathematical models provide important insights for public health decision-makers to enforce different mitigation strategies in different countries.…”
Section: Introductionmentioning
confidence: 99%